Cracking the Code of Musical Language: Making Sense of Rihanna’s “Diamonds” through Semiotics - Mlamli Diko (Universitas Sanata Dharma, 2025)
This article applies semiotics as a theoretical framework to uncover the observable layers of meaning that are interwoven in Rihanna’s song “Diamonds”. By examining the linguistic, visual, and musical elements of this song, this scholarly discourse aims to unearth the symbolic significance of “Diamonds” and their implications for contemporary popular music. Over and above this, it is to underscore that there is an intricate relationship between linguistics and musicology, hence the necessity to form an interdisciplinary dialogue. Ultimately, three notable findings are evident. First, the semiotic examination of Rihanna’s “Diamonds” reveals that the recurring motif of diamonds symbolizes more than just material wealth. Rather, diamonds serve as powerful metaphorical expressions of fortitude, strength, and enduring love. Second, through semiotic exposition, the use of light imagery, among others, conveys themes of conviction, optimism, and clarity. By the same token, references to shining bright like diamonds evoke notions of enlightenment and transcendence, sharply contrasting with the darker elements explored in the song’s lyrics. Third, this scholarly evaluation unmasks the synergistic relationship between linguistic and non-linguistic elements in “Diamonds”. Conclusively, the combination of words and music solidifies the overall message and emotional resonance of the song, creating a more immersive and impactful experience for the listener.